Elements of Apophatic Theology in the Writings of Elizabeth of the Trinity - Miczyński, Jan (Verbum Vitae, 2023)
The article is a theological and spiritual reflection on the spiritual doctrine of the French mystic St. Elizabeth of the Trinity OCD (Élisabeth Catez), who lived from 1880 to 1906. The present study seeks to explain the reason why apart from cataphatic (positive) expressions, characteristic of nuptial Carmelite mysticism, which Elizabeth represents, her writings sometimes contain apophatic (negative) expressions, emphasizing the unknowability of God. The historical and literary, hermeneutical, philological and comparative analyses of her work lead to the following conclusions; as a Carmelite she consciously referred to the teaching of the Areopagite (Pseudo-Dionysius the Areopagite) and to the later continuator of his thought, Bl. John Ruusbroec (Ruysbroeck); however, to apophatic expressions – e.g. infinite, unchanging, inaccessible, indescribable, immovable, inexhaustible, unknown, invisible, incomprehensible, incomparable, elusive – she gave a nuptial tone, for the sake of emphasizing the beauty and poetic nature of the bridal love of God and man. For this reason, Elizabeth does not represent the apophatic trend, but uses its language to emphasize the beauty of God and the poetic character of his relationship with man